2016
DOI: 10.1016/j.celrep.2016.04.066
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Small-Molecule BMP Sensitizer for Human Embryonic Stem Cell Differentiation

Abstract: Summary Sorely missing from the “toolkit” for directed differentiation of stem/progenitor cells are agonists of the BMP signaling pathway. Using a high throughput chemical screen, we discovered that PD407824, a checkpoint kinase 1 (CHK1) inhibitor, increases the sensitivity of cells to sub-threshold amounts of BMP4. We show utility of the compound in the directed differentiation of human embryonic stem cells toward mesoderm or cytotrophoblast stem cells. Blocking CHK1 activity using pharmacological compounds o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 51 publications
0
37
0
Order By: Relevance
“…Among those, importazole is a transport receptor importin-β ( 47 ) and AG 957 is a protein tyrosine kinase inhibitor ( 48 ). Moreover, brazilin is a NF-kappaB inhibitor ( 49 ) and PD 407824, a hepatoprotective agent, is known as Wee1/Chk1 inhibitor ( 50 ), whereas Ro 28-1675 is known as glucokinase activator ( 51 ). However, the action mechanisms of NCGC00182353-01 and NCGC00181381-01 were not identified yet ( Supplementary Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among those, importazole is a transport receptor importin-β ( 47 ) and AG 957 is a protein tyrosine kinase inhibitor ( 48 ). Moreover, brazilin is a NF-kappaB inhibitor ( 49 ) and PD 407824, a hepatoprotective agent, is known as Wee1/Chk1 inhibitor ( 50 ), whereas Ro 28-1675 is known as glucokinase activator ( 51 ). However, the action mechanisms of NCGC00182353-01 and NCGC00181381-01 were not identified yet ( Supplementary Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…4b), there is a difference with the non-canonical BMP4/TGF-B pathway. Though required to maintain pluripotency in mESC, BMP4 signalling promotes differentiation of primed PSCs 47 . Our data show increased expression in the ‘High’ Pluritest category of calcineurin, which is the catalytic subunit gamma of PP3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Myoblasts are derived from mesenchymal-derived precursors [38]. It has been reported that C2C12 myoblasts are reprogrammed into mature osteoblasts by the stimulation with bone morphogenetic proteins (BMPs) as BMP-2 and BMP-4 [39,40]. The common mesenchymal origin of L8 with the former cell lines possibly explains the detection of A7 antigen in L8 cells.…”
Section: Discussionmentioning
confidence: 99%